SCAF4 and SCAF8, mRNA anti-terminator proteins - Gregersen, LH; Mitter, R; Ugalde, AP; Nojima, T; Proudfoot, NJ; Agami, R; Stewart, A; Svejstrup, JQ (Cell Press, 2019)
Accurate regulation of mRNA termination is required for correct gene expression. Here, we describe a role for SCAF4 and SCAF8 as anti-terminators, suppressing the use of early, alternative polyadenylation (polyA) sites. The SCAF4/8 proteins bind the hyper-phosphorylated RNAPII C-terminal repeat domain (CTD) phosphorylated on both Ser2 and Ser5 and are detected at early, alternative polyA sites. Concomitant knockout of human SCAF4 and SCAF8 results in altered polyA selection and subsequent early termination, leading to expression of truncated mRNAs and proteins lacking functional domains and is cell lethal. While SCAF4 and SCAF8 work redundantly to suppress early mRNA termination, they also have independent, non-essential functions. SCAF8 is an RNAPII elongation factor, whereas SCAF4 is required for correct termination at canonical, distal transcription termination sites in the presence of SCAF8. Together, SCAF4 and SCAF8 coordinate the transition between elongation and termination, ensuring correct polyA site selection and RNAPII transcriptional termination in human cells.